A study of the long-term causal relationship between economic growth and public spending in Syria for the period (1990-2018). (Journal of Hama University, 2021)
The researhch aimed to study and analyze the nature of the relationship between public spending and economic growth in Syria during the period (1990-2018), where data related to time series were obtained based on the figures issued by the Ministry of Finance and the Syrian statistical group, and the study followed the descriptive approach using the method of analysis Standard statistical analysis in order to analyze the relationship between public spending and economic growth using the Eviews10 program, and the study used unit root tests and the Toda methodology, and relied on dynamic analysis by analyzing the components of variance and the immediate response function. The results of unit root tests revealed that the public spending variable is stable at the level. The gross domestic product is stable at the first difference, and Toda's results indicated the existence of a long-term relationship with one direction that moves from public spending to economic growth, which supports Keynes' hypothesis. It was observed through the estimation of the self-regression vector that there was a positive effect of both variables on each other. The shocks indicated the presence of positive effects between each of the two variables.